2000
DOI: 10.1046/j.1463-5224.2000.00126.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of single- and multiple-dose 0.5% timolol maleate on intraocular pressure and pupil size in female horses

Abstract: OBJECTIVE: To determine the effect of single and multiple-dose 0.5% timolol maleate on intraocular pressure (IOP) and pupil size between 8 AM and 8 PM. Animals Nine female horses with normotensive eyes. Procedure IOP, horizontal and vertical pupil size were measured on a single day, between 8 AM and 8 PM at hours 0, 0.5, 1, 2, 4, 6, 8, 10, and 12. A single dose of 0.5% timolol maleate was applied to both eyes immediately after the first measurement at 8 AM. IOP and pupil size were measured at 8 AM and 4 PM in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
2

Year Published

2004
2004
2020
2020

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 0 publications
2
17
2
Order By: Relevance
“…We found that the compounded ointment and commercially available solution formulations of dorzolamide(2%)–timolol(0.5%) had similar effects in both treated and untreated eyes. The approximately 13% reduction in IOP of treated eyes in our study is comparable to previous reports evaluating topical beta‐adrenergic antagonists and carbonic anhydrase inhibitors in horses, which have described 10–17% reduction in IOP . In our study, the magnitude of IOP reduction was greater in treated eyes compared to untreated eyes, but this difference was not significant.…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…We found that the compounded ointment and commercially available solution formulations of dorzolamide(2%)–timolol(0.5%) had similar effects in both treated and untreated eyes. The approximately 13% reduction in IOP of treated eyes in our study is comparable to previous reports evaluating topical beta‐adrenergic antagonists and carbonic anhydrase inhibitors in horses, which have described 10–17% reduction in IOP . In our study, the magnitude of IOP reduction was greater in treated eyes compared to untreated eyes, but this difference was not significant.…”
Section: Discussionsupporting
confidence: 85%
“…A baseline period of 2 days was selected for our study based on previous reports; notably, the mean IOP value obtained during our baseline period, 21.67 (3.47) mmHg, was within the range of previously reported normal values (17–28 mmHg), while those obtained during or after the treatment period approached the lower end of this range . Within the baseline period, IOP values on Day 2 were not significantly lower than those on Day 1; however, the descending trend in IOP values is readily observed (Figs and ).…”
Section: Discussionsupporting
confidence: 62%
See 2 more Smart Citations
“…Current glaucoma therapies reduce IOP medically or surgically . Medical therapy consists of topical beta blockers and/or topical carbonic anhydrase inhibitors applied 2–3 times daily to reduce aqueous humour production, and concurrent systemic and topical anti‐inflammatory therapy to control any underlying equine recurrent uveitis . However, based on 2 retrospective case studies on equine glaucoma, the long‐term success of medical management appears poor .…”
Section: Introductionmentioning
confidence: 99%